Ten Years of Tau-Targeted Immunotherapy: The Path Walked and the Roads Ahead - Novak, Petr; Kontsekova, Eva; Zilka, Norbert; Novak, Michal (Frontiers in Neuroscience, 2018)
Neurofibrillary pathology comprised of pathological tau protein is closely tied to a range of neurodegenerative disorders, the most common of which is Alzheimer's disease. While they are individually rarer, a range of other disorders, the tauopathies (including Pick's disease, progressive supranuclear palsy, corticobasal degeneration, and primary progressive aphasia) display pronounced underlying tau pathology. In all cases, the distribution and amount of tau pathology closely correlates with the severity and phenotype of cognitive impairment, and with the pattern and degree of brain atrophy. Successfully counteracting tau pathology is likely to halt or slow the progression of these debilitating disorders. This makes tau a target of prime importance, yet an elusive one. The diversity of the tau proteome and post-translational modifications, as well as pathophysiology of tau are reviewed. Beginning 2013, a range of tau-targeted immunotherapies have entered clinical development; these therapies, and their common themes and differences are reviewed. The manuscript provides an extensive discussion on epitope selection for immunotherapies against tau pathology, on immunological mechanisms involved in their action, and challenges such as immune senescence, vaccine design, or evolution of epitopes. Furthermore, we provide methodological recommendations for the characterisation of active vaccines and antibodies, animal models, and the target itself – the diseased tau proteome.